En sti er en sti – eller? Udvalgte resultater fra projektet Rum og rammer for aktivt udeliv - Arvidsen, Jan; Dalgaard, Karen; Andkjær, Søren (Forum for Idræt, 2013)
Research indicates that physical surroundings and outdoor facilities have an impact on peoples active outdoor recreation. Most research however has a quantitative approach, and there seems to be a lack of research and knowledge regarding people’s preferences and experiences of places related to their activity and their motives for being active in the outdoors. The study Rum og rammer for aktivt udeliv [Spaces for Active Outdoor Recreation]intends to study specific places and analyse how and why these places correspond to motives and needs from selected groups of users. Methods are case studies using observation and qualitative interviews. In this article we present selected results regarding motives for outdoor recreation and meanings and implications of paths to mountain bikers and runners. Results show both important differences and similarities with regard to motives and to meanings and implications of paths between mountain bikers and runners. The study underlines the importance of taking a qualitative approach looking at specific places and specific groups. It gives valuable knowledge to be used in planning and designing for active outdoor recreation with perspectives to improving people’s health and quality of life.